Tuning the spontaneous formation kinetics of caffeine : malonic acid co-crystals. Issue 15 (23rd March 2016) - Nartowski, K. P.; Khimyak, Y. Z.; Berry, D. J.
Abstract : It has previously been reported that the caffeine : malonic acid co-crystal system forms spontaneously upon the contact of the two materials, here we explore the mechanism of this formation and control the kinetics to enable us to monitor the conversion. Abstract : It has previously been reported that the caffeine : malonic acid co-crystal system forms spontaneously upon the contact of the two materials. Here we studied the crystal growth in this system to rationally define the role that water plays, thus enabling us to monitor the conversion by solid-state NMR and control the kinetics of spontaneous co-crystal production by increasing or decreasing the relative humidity.